Towards data-driven next-generation transmission electron microscopy - Jones, Lewys (My University, 2020)
Electron microscopy touches on nearly every aspect of modern life, underpinning materials development for quantum computing, energy and medicine. We discuss the open, highly integrated and data-driven microscopy architecture needed to realize transformative discoveries in the coming decade.
Keywords: Electron microscopy; data-driven; architecture; Electron microscopy; data-driven; architecture